“Rien pour la révolution, tout par l’éducation”: The Talented Tenth at the Second Pan-African Congress - Emanuele Nidi (European Journal of American Studies)
The Second Pan-African Congress of 1921 was an international meeting organized around three sessions in three different European capitals (London, Brussels, and Paris). Notwithstanding its moderate program, colonial powers regarded it as an offshoot of Bolshevik and Garveyite propaganda. These allegations sparked a fierce internal debate between the French Pan-African leader Blaise Diagne and the US delegation, the former accusing the latter of being too critical of colonialism. However, the US delegates were mainly members of the Black bourgeoisie, hardly accountable for the radicalism denounced during the Congress sessions. They exemplified a depiction of the intellectual elite described by their leader, W.E.B. Du Bois, in his influential writings on the “Talented Tenth.” Based on an analysis of the US delegation, this article examines the characteristics of early Pan-Africanism and the ambiguous relationship between the Pan-African Congress and the European colonial powers.